Psychometric Evaluation of the Chinese Version of the Modified Online Compulsive Buying Scale among Chinese Young Consumers. Issue 2 (3rd April 2021) - She, Long; Sharif, Saeed Pahlevan; Nia, Hamid Sharif
ABSTRACT: This study aimed to examine the psychometric properties of the Chinese translation of the modified online compulsive buying scale. A convenience sample of 539 Chinese university students were recruited in four major cities in China. The scale was translated from English to Chinese using forward-backward method. Performing a maximum likelihood exploratory factor analysis revealed one factor consisting of 10 items, which was confirmed by conducting a confirmatory factor analysis. Reliability, face validity, content validity, and construct validity of the scale were assessed. The Chinese version of the modified online compulsive buying scale showed good internal consistency (Cronbach's alpha = .909), and good construct reliability (composite reliability = .911, maximal reliability = .919, McDonald's omega = .910). Moreover, convergent validity of the scale was established (average variance extracted = .510). The validated instrument can be used in future studies to measure young consumers' online compulsive buying behavior in China.